Psychometric Properties of the OREA-Mx Psychological Capital Scale in Older Mexican Adults. - Serrano-Cena, Alba; Santana-Cárdenas, Soraya; Castro Zazueta, Nancy Pamela (Salud Mental)
Introduction: Psychological capital includes components of optimism, resilience, hope and self-efficacy with an impact on psychological well-being. Objective: To assess the psychometric properties of the OREA instrument measuring psychological capital and to analyze the relationship between this construct and its dimensions and depression in a sample of older adults in Mexico. Method: Quantitative, cross-sectional, non-experimental study. A total of 314 older adults (> 60) completed the sociodemographic data and cognitive impairment, psychological capital and depression scales. The mean age was 75.46 (SD = 8.382), 74.2% were female and 28.7% had completed elementary school. Clinical depression was present in 23.2%. Results: Statistical analysis was performed using R Studio software version 2023.09.1+494. The Chi-square model fit (χ) corroborated the four-factor structure of the instrument (Model 1) and the general scale of the instrument (Model 2), obtaining adequate fit indices (Model 1= χ/gl = 1. 05; GFI =.99; CFI = 1, TLI = 1; RMSEA =.04 and SRMR =.04 and Model 2= χ/gl = 1.06; GFI =.99; CFI = 1, TLI = 1; RMSEA =.04 and SRMR =.03). Cronbach's Alpha and McDonald's Omega coefficients were greater than.70. There is a significant negative correlation between psychological capital and its dimensions and depression Discussion and conclusion: The OREA-Mx version is a preliminary scale with adequate reliability in its second-order factor integrating the four dimensions for Mexican older adults. The correlation between psychological capital through four dimensions with depression is negative and significant, showing the protective nature of psychological capital against depression.